2009
DOI: 10.1097/mpa.0b013e318198283b
|View full text |Cite
|
Sign up to set email alerts
|

Early Inhibition of Prostaglandin Synthesis by n-3 Fatty Acids Determinates Histologic Severity of Necrotizing Pancreatitis

Abstract: Parenteral therapy with n-3 fatty acids decreased histopathologic severity in ANP by early inhibition of prostaglandin (E2 and F1alpha) synthesis and reduction of lipid peroxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…Our data also corroborate with a previous study reporting lower lipid peroxidation in the liver of rats receiving exclusive parenteral nutrition and rats with necrotizing pancreatitis receiving FOLE. 6,37 Our data also are in tune with those of a previous study reporting a lower risk for peroxidation in patients receiving home parenteral nutrition with FOLE, regardless of the presence of comorbidities. 38 However, our findings are not in agreement with a study observing that in patients with type 2 diabetes mellitus, F2-isoprostane concentrations were not affected by a FOLE.…”
Section: Discussionsupporting
confidence: 89%
“…Our data also corroborate with a previous study reporting lower lipid peroxidation in the liver of rats receiving exclusive parenteral nutrition and rats with necrotizing pancreatitis receiving FOLE. 6,37 Our data also are in tune with those of a previous study reporting a lower risk for peroxidation in patients receiving home parenteral nutrition with FOLE, regardless of the presence of comorbidities. 38 However, our findings are not in agreement with a study observing that in patients with type 2 diabetes mellitus, F2-isoprostane concentrations were not affected by a FOLE.…”
Section: Discussionsupporting
confidence: 89%
“…237 ). It has been demonstrated that the effect of LC n-3 PUFA on pancreatic function may be mediated by inhibition of PG and pro-inflammatory cytokine synthesis 238,239 . Particularly, the anticarcinogenic properties of LC n-3 PUFA, which are mainly attributed to altered PG formation due to COX-2 inhibition, may prove beneficial in pancreatic cancer 240 .…”
Section: Critically Ill Patients Cancer and Other Chronic Diseasesmentioning
confidence: 99%
“…Відносний сумарний вміст ПНЖК ро-дини ω-6 також зменшується через 3 доби на 13% , а через 7 діб на 16% внаслідок знижен-ня відносного вмісту С 18:2 (ω-6) -лінолевої кислоти на 21 та 25% у відповідні терміни. Відомо, що зниження вмісту лінолевої кис-лоти, попередника біосинтезу арахідонової кислоти, із послідуючим циклооксигеназним її метаболізмом супроводжується утворенням прозапальних медіаторів: лейкотрієнів, зо-крема ЛтВ 4 , простагландинів E 2 та F1α [30]. Одержані дані свідчать про те, що у ПЗ за ГП відбуваються зміни жирнокислотного складу ліпідів.…”
Section: рис 7 активність фла 2 у плазмі крові щурів за гострого паunclassified